In vitro susceptibility testing of four antifungal drugs against fungal isolates in onychomycosis - Kulkarni, Smita S.; Bhakre, Jayshree B.; Damle, Ajit S. (International Journal of Research in Medical Sciences, 2018)
Background: Onychomycosis is chronic fungal infection of fingernails and toenails. Variety of fungi cause onychomycosis. Due to importance of high prevalence rate of onychomycosis this study was conducted. Methods: In this study 100 patients suspected of onychomycosis were examined. Diagnosis of onychomycosis was based on the patient’s history, physical examination, microscopy and culture of nail specimens. Results: Direct microscopy of the nail clippings in 20% KOH solution was positive in 61% and culture was positive in 54% cases. The common etiological agent was dermatophytes (79.6% cases) followed by non dermatophyte moulds (11.1% cases) and yeasts (9.2% cases). Amongst dermatophytes, T. rubrum was found to be commonest etiological agent (57.6%) followed by T. mentagrophytes. We had performed the in vitro antifungal susceptibility testing of isolated fungal species against Amphotericin B, Fluconazole, Itraconazole and Terbinafine according to standard guidelines recommended by the CLSI. Antifungal susceptibility testing of dermatophytes and non-dermatophyte moulds was performed by broth macrodilution method. For Candida species we used broth macrodilution method as well as disk diffusion method. All three Candida albicans isolates were sensitive to amphotericin B, fluconazole and itraconazole. Two strains of Candida krusei were sensitive to amphotericin B and resistant to fluconazole and itraconazole. Two isolates of T. rubrum had MIC >64µg/ml and one T. Mentagrophytes isolate had MIC 32µg/ml for fluconazole. Among non dermatophyte moulds, Aspergillus niger and one isolate of Fusarium oxysporum showed high MICs against fluconazole. Conclusions: Terbinafine exhibited the lowest MICs among all the tested antifungal drugs.